Vitamin A Supplementation and Stunting Levels Among Two Year Olds in Kenya: Evidence from the 2008-09 Kenya Demographic and Health Survey - Kimani-Murage, Elizabeth W.; Ndedda, Crispin; Raleigh, Katherine; Masibo, Peninah (International Journal of Child Health and Nutrition, 2013)
Background: High levels of undernutrition, particularly stunting, have persisted in Kenya, like in other developing countries. The relationship betweeen vitamin A supplementation and growth of children in Kenya has not been established, while there are context-specific variations on the relationship. This study explores this relationship in the Kenyan context. Methods: The study uses data from the 2008-09 Kenya Demographic and Health Survey, involving children aged 24-35 months, a weighted sample of 1029 children. Descriptive and logistic regression analyses were conducted. The outcome variable of interest is stunting, while the exposure variable of interest is ever receiving a dose of vitamin A supplement. Secondary outcomes include underweight and wasting status. Results: The prevalence of stunting in the study group was 46%; underweight 20%; and wasting 6%. The prevalence of ever receiving vitamin A supplement was 78%. Receiving vitamin A supplement was significantly negatively associated with stunting and underweight status, adjusting for other co-risk factors. The odds of stunting were 50% higher (p=0.038), while for underweight were 75% higher (p=0.013) among children who did not receive Vitamin A supplement compared with those who did. Conclusion: This study demonstrates that receiving vitamin A supplement may be beneficial to growth of young children in Kenya. However, though freely offered through immunization services to children 6-59 months, some children do not receive it, particularly after completing the immunization schedule. There is need to establish innovative and effective ways of maximizing utilization of this intervention, particularly for children who have completed their immunization schedule.